Effect of Shared Leadership and Employees’ Creativity: Meaning at Workplace as a Mediation - Muhammad Rasyid Abdillah; Rizqa Anita; Edwin Aditya Nugraha; Giri Suseno; Nor Balkish Zakaria (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: This study aims to discover more about the relationship between shared leadership and employees’ creativity. Background Problems: The main question of this research is whether shared leadership enhances employees' creativity via meaningful at a workplace. Novelty: Empirical evidence that explains how shared leadership may enhance employees’ creativity in the Indonesian context, especially in Indonesian technology companies is unexplored. Thus, a study that discovers such a mechanism is still needed. Research Methods: This study collected surveys with these employees by utilizing the convenience random sampling technique and utilizing PLS analysis to test hypotheses. Finding/Results: This study reveals that shared leadership affects employees’ creativity. Furthermore, the study finding also explains that meaning at the workplace mediates the link between shared leadership and employees’ creativity. Conclusion: The study finding provides an additional contribution, namely the importance of the shared leadership function in shaping positive employee behavior in the organization.